Data Warehouse Design Acceptance of Goods In PT Transmart Using Tools Pentaho and Tableu - Emi Purwati; Syam Gunawan (Jurnal SIMADA (Sistem Informasi dan Manajemen Basis Data), 2018)
The purpose of this research is to process the data of receipt of goods at PT Transmart Central Park, analyze the existing database in the information system of receipt of goods to get the necessary information and design the data warehouse to integrate the existing data so that obtained information to take a decision. Business Intelligence (BI) is one of information technology that can be solution to collect, store and analyze company data. Online Analytical Processing (OLAP) consists of a set of tools in use to help the process of analysis and comparison of data in the database. OLAP tools and methods help users analyze data in a data warehouse by providing a variety of dynamic graphical display data. The data warehouse design method is implemented by applying the 9 steps (Nine-Step Methodology) used by Ralph Kimball in designing the star scheme. The results achieved are data warehouse that provides the desired information and provide summary information in the form of tables and charts, can be compared between the purchase order data with receiving report is global, relevant, and integrated that can be seen from various points of view so useful for the leaders to make a decision.Keywords: Bussines Intelligent; Data Warehouse; OLAP; Nine-Step Methodology